Environment NGO Activity in the World Political Arena - O. Y. Semenov (Vestnik MGIMO-Universiteta)
The globalization of ecological and environmental problems in contemporary world politics defines a significant role of such issues in the agenda of both state and non-state international actors. Traditional diplomacy needs the assistance of NGOs related to environment and creating new mechanisms which could be able to respond to rapid ecological changes. The new role of environmental NGOs in world politics is clearly evident in rule- and standard-making as well as global governance issues.